2013
DOI: 10.1111/j.1526-100x.2012.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Stress‐Gradient Hypothesis During the Restoration of Tropical Degraded Land Using the Shrub Rhodomyrtus tomentosa as a Nurse Plant

Abstract: The relative importance of facilitation and competition between pairwise plants across abiotic stress gradients as predicted by the stress-gradient hypothesis has been confirmed in arid and temperate ecosystems, but the hypothesis has rarely been tested in tropical systems, particularly across nutrient gradients. The current research examines the interactions between a pioneer shrub Rhodomyrtus tomentosa (the nurse plant) and seedlings of a transplanted native woody Schima superba (the target species) in a tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Our previous study also indicated that species chosen for their shade tolerance could accelerate restoration (Yang et al 2010 a ). In similar transplantation studies, the successful establishment of native plant seedlings was closely associated with species‐specific traits in South China, especially shade tolerance (Wang et al 2009 a ; Liu et al 2013 a ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our previous study also indicated that species chosen for their shade tolerance could accelerate restoration (Yang et al 2010 a ). In similar transplantation studies, the successful establishment of native plant seedlings was closely associated with species‐specific traits in South China, especially shade tolerance (Wang et al 2009 a ; Liu et al 2013 a ).…”
Section: Discussionmentioning
confidence: 94%
“…The balance is generally altered by changes in abiotic factors. For example, interspecific interaction switches between competition and facilitation along the stress gradient due to changes in aridity (Callaway et al ; Barnes & Archer ; Sthultz et al ), altitude (Yang et al 2010 b ; Wang et al ), soil nutrients (Liu et al 2013 a ), and precipitation (Maestre & Cortina ). Nevertheless, the influences of biotic factors in switching between competition and facilitation in interspecific interactions are seldom mentioned (Debain et al ; Graff et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Microenvironmental changes that occur on shrub islands include temperature buffering (Drezner, 2004(Drezner, , 2007, shading (Ishii et al, 2006;Smit et al, 2008), increased soil moisture (Callaway et al, 1996;Callaway, 2007), and soil amelioration (Carrillo-Garcia et al, 2000a;Wang et al, 2011). In our previous study, the shrub islands created by R. tomentosa improved soil physical characteristics (e.g., reduced soil bulk density and increased soil moisture content), reduced soil nutrients (e.g., soil organic matter and total nitrogen), and provided shading (reduced by 87·3% total radiation), relative to open spaces (Yang et al, 2010;Liu et al, 2013). As noted earlier, a shrub island can simultaneously exert both positive and negative effects on other plants growing on the island (Armas & Pugnaire, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…In our previous study, the shrub islands created by R . tomentosa improved soil physical characteristics (e.g., reduced soil bulk density and increased soil moisture content), reduced soil nutrients (e.g., soil organic matter and total nitrogen), and provided shading (reduced by 87·3% total radiation), relative to open spaces (Yang et al ., ; Liu et al ., ; Liu et al ., ). As noted earlier, a shrub island can simultaneously exert both positive and negative effects on other plants growing on the island (Armas & Pugnaire, ).…”
Section: Discussionmentioning
confidence: 97%
“…Positive plant-plant interactions become more frequent or intense with increasing moisture stress, a common and pervasive type of abiotic stress (Holmgren et al 1997, Reisner 2010, Ziffer-Berger et al 2014; but see Maestre et al 2005). Under high moisture stress, a "nurse" plant may benefit a neighboring beneficiary plant by improving soil moisture conditions (Chambers 2001, Maestre et al 2001, mediating soil temperatures and reducing evapotranspiration (Moro et al 1997, Ramírez et al 2015, enhancing soil nutrient availability (Liu et al 2013) and organic matter (Ramírez et al 2015), or decreasing solar radiation (Valiente-Banuet and Ezcurra 1991, Maestre et al 2001). At very high levels of abiotic stress (e.g., extreme drought), however, facilitative effects of neighbors on beneficiaries can be outweighed by competition for severely limited resources (Tielbörger and Kadmon 2000).…”
mentioning
confidence: 99%